Comparative analysis of Poisson's ratio of 2D woven constructions and their composites produced from different auxetic geometries. Issue 3 (9th December 2022) - Shukla, Shivangi; Behera, Bijoya Kumar
Abstract: Auxetic materials exhibit some unconventional properties such as improved toughness, resilience, shear resistance, impact resistance, fracture resistance, synclastic behavior, shape fitting ability, sound absorption, and vibration damping owing to their negative Poisson ratio. Auxetic woven fabrics may be made using both auxetic and non‐auxetic yarns. This article focuses on the development and analysis of Poisson's ratio of woven fabrics and their composites based on different auxetic geometries. Some innovative auxetic geometries are developed and fabrics are woven based on these geometries. Auxetic fabric samples and their composites are characterized for their Poisson's ratio values to ascertain the potential of different geometries to produce auxetic woven structures. It is concluded that the auxeticity of the auxetic woven fabric is largely dependent on the weave designs. Also, the auxeticity can be introduced into the composite using woven auxetic preform. Abstract :